2017
DOI: 10.2478/prilozi-2018-0008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Role of ABCB1gene Polymorphic Variants on Psychiatric Disorders Predisposition in Macedonian Population

Abstract: The psychiatric and other CNS disorders are characterized with unregulated neuro-inflammatory processes and chronic microglia cell activation resulting with detrimental effect. ABCB1gene polymorphismsC1236T, G2677T/Aand C3435T are associated with P-glycoprotein expression and function andare linked with predisposition to psychiatric disorders such as schizophrenia and bipolar disorders. The relationship between mood disorders and glucocorticoids has been confirmed and ABCB1 SNPs influence the glucocorticoids a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…For the P-glycoprotein polymorphisms, Turgut et al (2009) found a deviation from equilibrium in the C3435T polymorphism, indicating a possible association between BD and p-glycoprotein structure (p<0.01). Naumovska et al (2017) found an uneven distribution of p-glycoprotein polymorphisms only in women, with the alleles 1236 and 2677 being potential risk polymorphisms for BD in women (p<0.05). In the case of cell adhesion molecule genes, 22 significant risk genes were identified (See Table 5).…”
Section: Resultsmentioning
confidence: 94%
“…For the P-glycoprotein polymorphisms, Turgut et al (2009) found a deviation from equilibrium in the C3435T polymorphism, indicating a possible association between BD and p-glycoprotein structure (p<0.01). Naumovska et al (2017) found an uneven distribution of p-glycoprotein polymorphisms only in women, with the alleles 1236 and 2677 being potential risk polymorphisms for BD in women (p<0.05). In the case of cell adhesion molecule genes, 22 significant risk genes were identified (See Table 5).…”
Section: Resultsmentioning
confidence: 94%